1988
DOI: 10.1063/1.340343
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation density reduction through annihilation in lattice-mismatched semiconductors grown by molecular-beam epitaxy

Abstract: Epitaxial InAs/GaAs, GaAs/Ge/Si, GaAs/InP, and InAs/InP heterostructures are grown by molecular-beam epitaxy. Transmission electron microscopy studies reveal that, for these heteroepitaxial systems, the threading dislocation density is inversely proportional to the epilayer thickness. At a given thickness, the threading dislocation density is relatively insensitive to lattice mismatch (3.2%<‖Δa‖/a<7.2%), to differences in thermal expansion coefficients (6.9×10−7<‖Δα‖<3.4×10−6 K−1), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 8 publications
6
37
0
Order By: Relevance
“…For the directly grown samples (a) and (b), we observe that D is inversely proportional to x. This is explained by the pairannihilation mechanism of TDs and consistent with previous reliable reports [8][9][10]. The behavior of D dominated by the pair-annihilation mechanism is described by a differential equation…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…For the directly grown samples (a) and (b), we observe that D is inversely proportional to x. This is explained by the pairannihilation mechanism of TDs and consistent with previous reliable reports [8][9][10]. The behavior of D dominated by the pair-annihilation mechanism is described by a differential equation…”
Section: Methodssupporting
confidence: 83%
“…In fact, for InGa(Al)As with indium contents less than $0.5, the graded-buffer growth is effective to reduce the near-surface threading dislocation (TD) density in comparison with the direct growth. A TD density less than $10 8 cm À2 can be obtained by the graded buffers of $1.0 mm thickness [6], while the direct growth gives $10 9 cm À2 for $1.0 mm thickness [8]. However, the fundamental mechanism of the reduction of the TD density by the graded buffers is not quite clear.…”
Section: Introductionmentioning
confidence: 95%
“…!in thti&fless. ZZ7 reduction has also been reported for InAs/GaAs, GaAs/Ge/Si, GaAs/InP, and InAsfinP by Sheldon et al [3], showing similar l/h dependence for all 4 material systems. They found TD density to be inversely proportional to film thickness for initial TD densities of 108-109 cm-*.…”
Section: Introductionsupporting
confidence: 50%
“…The authors used this model successfully to explain the 1/h -scaling behavior observed experimentally in several cubic materials by Sheldon et al 38 We applied this model to our experimental data from HVPE GaN layers presented in Fig. 5.…”
Section: Extended Defects Misfit Dislocationsmentioning
confidence: 99%